Pengaruh Penjualan Online Di Era Pademi Covid-19 Terhadap Perkembangan UMKM Batik Jetis Di Sidoarjo - Nur Hidayah; Eka Adiputra (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2022)
This study aims to determine how big the influence of online sales during the Covid-19 pandemic on Batik Jetis UKM. All activities are carried out online or online to avoid crowds. Of course, this situation has an impact on the Indonesian economy, especially in the UMKM sector. The decline in the turnover of UMKM actors is very significant, including the business field for providing written batik. Online sales are a strategy as well as a means of boosting economic life during a pandemic. The method for obtaining data in this study is a qualitative approach with direct interviews with resource persons, namely the business actors of Batik Jetis and also a SWOT analysis. During this pandemic, UMKM are very influential because they can stabilize the Indonesian economy. Collaboration by UMKM by collaborating with platforms, marketplaces and social media is very helpful as a media for marketing, promotion and online sales.